Isolation, identification, and phylogenetic analysis of subgroup III strain of bovine respiratory syncytial virus contributed to outbreak of acute respiratory disease among cattle in Northeast China. Issue 1 (1st January 2021) - Jia, Shuo; Yao, Xin; Yang, Yaqi; Niu, Chao; Zhao, Yi; Zhang, Xiaomei; Pan, Ronghui; Jiang, Xiaoxia; Xiaobo, Sun; Qiao, Xinyuan; Guan, Xueting; Xu, Yigang
ABSTRACT: Bovine respiratory syncytial virus (BRSV) is a clinically important causative agent of acute respiratory diseases in postweaning calves and feedlot cattle and causes numerous economic losses to the cattle industry. In June 2018, an outbreak of an acute respiratory disease occurred among 4- to 10-month-old calves on three intensive beef cattle farms in Heilongjiang Province, Northeast China, with a 27.42% morbidity rate (329/1200) and a > 25% mortality rate (85/329). Using next-generation sequencing, we comprehensively analyzed microbial diversity in the lung samples of the diseased cattle and found that the causative agent of this epidemic outbreak is mainly a bovine orthopneumovirus named BRSV strain DQ. We then isolated and confirmed the virus by RT-PCR and an indirect immunofluorescence assay. Phylogenetic analysis of genes G, F, N, NS1, NS2, and SH of BRSV strain DQ showed that this strain shares the highest genetic similarity with strains USII/S1, 15489, V41, and NY487834 belonging to subgroup III of BRSV. This is the first report of subgroup III strain of BRSV presence in China. Heilongjiang Province is a major cattle-breeding province in China; therefore, it is necessary to test for BRSV in the cattle trade and to conduct region-extended epidemiological surveillance for BRSV in China.